Pharmacological nephrotoxicity profile in a comprehensive cancer center: What changed in two decades and predictors for the need for haemodialysis and mortality - André Ferreira; Marina Reis; Teresa Chuva; Hugo Ferreira; Inês Coelho; Ana Paiva; José Maximino Costa (Nefrología)
Introduction and objectives: Acute kidney injury (AKI) is a frequent and severe complication in hospitalised cancer patients. However, overall data from in-hospital drug-related AKI in cancer patients is scarce. We aim to review the profile of moderate to severe drug-induced AKI in patients admitted to an oncology hospital over the last two decades and to assess renal and overall outcomes. Material and methods: 410 cases of drug-induced AKI KDIGO ≥ 2 were analyzed, comparing between two decades from 2002 to 2021 in a comprehensive cancer center. Results: The main differences were the introduction of new classes of cancer therapy (e.g., immune checkpoint inhibitors [ICPI] and tyrosine kinase inhibitors [TKI]), a decrease in nephrotoxicity due to platinum-based drugs, and an increase in nephrotoxicity caused by multiple drugs without cancer-directed therapy. Mortality was similar, but the need for haemodialysis (HD) was higher in the second decade (25.5% vs 36.6%, p = 0.02). Multivariate analysis presented invasive mechanical ventilation and sepsis as risk factors for both HD and mortality, haematologic cancer as risk factors for HD, and the need for HD and multiple drugs without cancer-directed therapy as risk factors for mortality. Conclusion: Adequate drug surveillance and prophylaxis render cancer therapy as a relatively small contributor to drug-induced AKI in a comprehensive cancer center. Critically ill patients have a higher need for HD and mortality regardless of the nephrotoxic agent implied. Resumen: Antecedentes y objetivos: La lesión renal aguda (LRA) es una complicación frecuente y grave en pacientes con cáncer hospitalizados. Sin embargo, los datos generales sobre la LRA relacionada con fármacos en pacientes con cáncer durante la hospitalización son escasos. Nuestro objetivo es revisar el perfil de la LRA moderada a grave inducida por fármacos en pacientes ingresados en un hospital oncológico durante las últimas dos décadas y evaluar los resultados renales y generales. Materiales y métodos: Se analizaron 410 casos de LRA KDIGO≥ 2 inducida por fármacos, comparando entre dos décadas de 2002 a 2021 en un comprehensive cancer center. Resultados: Las principales diferencias fueron la introducción de nuevas clases de terapia contra el cáncer (p. ej., inhibidores de puntos de control inmunitarios [ICPI] e inhibidores de la tirosina quinasa [TKI]), una disminución de la nefrotoxicidad debido a fármacos basados en platino y un aumento de la nefrotoxicidad causada por múltiples fármacos sin terapia dirigida al cáncer. La mortalidad fue similar, pero la necesidad de hemodiálisis (HD) fue mayor en la segunda década (25,5% vs 36,6%, p= 0,02). El análisis multivariante presentó la ventilación mecánica invasiva y la sepsis como factores de riesgo tanto para HD como para mortalidad, el cáncer hematológico como factores de riesgo para HD y la necesidad de HD y múltiples fármacos sin terapia dirigida al cáncer como factores de riesgo para mortalidad. Conclusiones: La adecuada vigilancia farmacológica y la profilaxis hacen que el tratamiento del cáncer sea un contribuyente relativamente pequeño a la LRA inducida por fármacos en un comprehensive cancer center. Los pacientes críticamente enfermos tienen una mayor necesidad de HD y mortalidad independientemente del agente nefrotóxico implicado.